A Highly Emissive Water‐Soluble Phosphorus Corrole. Issue 4 (9th December 2016) - Naitana, Mario L.; Nardis, Sara; Pomarico, Giuseppe; Raggio, Michele; Caroleo, Fabrizio; Cicero, Daniel O.; Lentini, Sara; Prodi, Luca; Genovese, Damiano; Mitta, Saisameera; Sgarlata, Anna; Fanfoni, Massimo; et al.
Abstract: The synthesis, spectroscopic, and optical properties of the water‐soluble phosphorus complex of a 2‐sulfonato‐10‐(4‐sulfonatophenyl)‐5, 15‐dimesitylcorrole have been investigated. The compound was prepared by adopting a novel strategy for the corrole sulfonation, leading to the regioselective isomer in an almost quantitative yield. The phosphorus coordination has a key role in determining the corrole substitution pattern, limiting the formation of poly‐substituted species, which affected the reaction of the corrole free base. The resulting complex shows excellent optical properties in terms of emission quantum yield, also in polar protic solvents, including water. 31 P NMR spectroscopy in CD3 OD indicates that the P sulfonate complex has been isolated in a hexacoordinated geometry with two different ligands (L1=‐OH, L2=‐OCH3 ), and it is prone to axial ligand exchange with methanol, with no evidence of intermediate pentacoordinated species. The morphological characterization of thin layers of the P corrole deposited onto an Au(111) surface showed that the addition of an intermediate layer of reduced graphene oxide allows for a better control of corrole aggregation, inducing also transformation of the Au(111) reconstructed surface. Abstract : Phosphorus is needed : The regioselective sulfonation of a triaryl corrole has been carried out with a novel strategy, where phosphorus coordination plays a key role in determining the corrole substitution pattern. The complex shows a high brightness in water, making it promising for sensor applications.